THE WORK VALUES AS IDENTITY-ANCHORING MECHANISMS: Career Women in Mission-Driven Microfinance Institutions - Nancy Yusnita; Doni Wihartika; Hari Gursida; Chih Seong SU (Amal Insani Foundation, 2026)
This study investigates how work values operate as identity-anchoring mechanisms that shape turnover intention among career women employed in microfinance institutions (MFIs). Rather than treating work values as static motivational preferences, the study conceptualizes them as identity-relevant cognitive frameworks that stabilize employment decisions in purpose-driven financial settings. A cross-sectional survey was administered to 800 employees working in microfinance institutions, 99.5% of whom were women. Work values were operationalized across three domains—personal, social–cultural, and organizational. Turnover intention was measured using multi-item Likert scales. Descriptive and comparative analyses were conducted to determine value salience and withdrawal cognition patterns. All work-value domains were strongly endorsed, with sociocultural values emerging as the most salient. Despite respondents’ relatively short organizational tenure and early-career status, turnover intention remained low. The findings suggest that socially embedded work values may function as identity anchors that mitigate withdrawal cognition in relational, mission-driven financial contexts. The cross-sectional and descriptive design constrains causal interpretation. Future research should test mediating mechanisms—such as meaningful work and identity integration—using longitudinal or structural modeling approaches. Retention strategies in microfinance organizations should emphasize purpose alignment, relational leadership, and structured identity development rather than relying predominantly on economic incentives. This study advances work value research by integrating identity theory with value congruence models and specifying gender-sensitive mechanisms within a female-dominated service sector